"Wit" Teaching About Death, Dying, Clinical Trials, and DNR - Jeffrey Spike; Christie Sain (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a small-group activity aimed to facilitate discussions after a viewing of the Emmy award-winning movie "Wit." The facilitator's guide and accompanying materials will enable faculty to lead small groups to effectively discuss breaking bad news, death and dying, do-not-resuscitate (DNR) orders, and clinical research trials after showing the movie. Methods A student handout, paper topics, and exam questions are included. It is strongly recommended that this lesson be timed to coincide with the students' advanced cardiovascular life support training, as it includes discussion of when to raise the question of DNR with patients based on realistic outcomes of CPR for patients with an underlying life-threatening illness. Results This activity has been a required 3-hour-long class for second-year medical students for the past 3 consecutive years. The movie is very effective in dramatizing the human toll that results from poor informed consent and deferring the DNR discussion. Discussion The small groups give students a chance to process their feelings and apply them to both the clinical ethics topics (DNR, palliative care) and the research ethics topics (informed consent, therapeutic misconception, right to withdraw from a study). The only limitation to this resource is that instructors must buy or rent a copy of the film.